Peran Guru Bimbingan dan Konseling dalam Mengembangkan Kecerdasan Spiritual Siswa SMP - Hapni, Elida; Fitri, Novita; Masril, Masril (JIGC (Journal of Islamic Guidance and Counseling), 2022)
This study aims to describe how the role of guidance and counseling teachers in developing spiritual intelligence of junior high school students. This research method uses descriptive qualitative research methods with data collection techniques using interviews and observations. The results of the study indicate that the role of Guidance and Counseling Teachers in Developing Spiritual Intelligence of Junior High School Students is to apply religious values, instill the values of honesty, patience education and train students to always be grateful. All of these roles are integrated into the process of guidance and counseling services in junior high schools. To develop students' spiritual intelligence, of course, it takes time in each process, so the support from all parties in SMP is very helpful in the process of developing spiritual intelligence of SMP students.